Judgments of Meaning in Life, Religious Beliefs, and the Experience of Cognitive (Dis)Fluency. Issue 3 (29th January 2015) - Davis, William E.; Hicks, Joshua A.
Abstract: The primary aim of the current studies was to test whether religiousness interacted with self‐reported levels of meaning in life (MIL) to predict the ease or difficulty in judging one's MIL, the search for meaning itself, and religious doubt. Undergraduate students in Study 1 ( N = 111) and adult participants recruited online in Study 2 ( N = 206) completed measures of religious beliefs, MIL, cognitive fluency related to MIL, and related variables. Study 3 merged these data sets. In Study 4 ( N = 255), online participants completed measures of religious beliefs, cognitive fluency related to religious beliefs, and MIL. Studies 1 and 2 showed that highly religious people with lower MIL reported greater difficulty making their MIL judgments than other people. Study 3 showed that they were also more likely to search for MIL and that disfluency mediated this effect. Study 4 demonstrated that they also reported more difficult judgments of religious beliefs and more religious doubts than their religious peers with high MIL. The current studies demonstrate that the experience of ease or difficulty associated with MIL judgments represents an important yet largely unexamined aspect of MIL. Our findings have implications for understanding the cognitive mechanisms underlying responses to meaning threats.